PENGARUH MINYAK CUMI PADA UMPAN BUBU DASAR TERHADAP HASIL TANGKAPAN IKAN-IKAN KARANG - Reppie, Emil (Sam Ratulangi University, 2010)
Bottom trap have been used widely by coastal communities in North Sulawesi to catch coral fishes, since it simple in design, cheaper and easy to manage with a small boat. Unfortunately, the fishing practice of the traditional trap is usually conducted in destructive way, where fishermen cover the gear with live coral to attract fishing target.Â Although the gearâ€™s design has evolved over centuries, there is still potential for improving its catching efficiency and selectivity. An attempt to understand the fishing process of bottom trap should therefore be focused on bait and how its chemical composition, visual and physical properties may stimulate target species to attack the bait and captured. Addition of squid liver oil to the bait could increase the fishing power of bottom trap gear. But scientific informationâ€™s about its applications are not available yet. Therefore, the objective of this research was to study the effect of squid liver oil on bait of bottom trap toward the capture of coral fishes. This research was done in Bangka Strait North of Minahasa, based on experimental method. Six units of bottom trap (bamboo) were operated ten nights in collecting data; where tree units of them used scad mackerel bait that injected by squid liver oil, and tree other units just used scad mackerel bait without squid liver oil; and the capture data were analyzed by ttest. The catch was 117 fish in total consist of 2 genera; 74 fish was caught by scad mackerel bait with squid liver oil, and 43 fish was caught by bait without squid liver oil. Analysis of ttest show that t0= 8.908>t0.05; 5= 3.250; which means that the addition of squid liver oil on bait could increase the catch of bottom trap.